The UK Government’s COVID-19 Policy: What Does “Guided by the Science” Mean in Practice? - Cairney, Paul (Frontiers in Political Science, 2021)
UK government ministers state that their COVID-19 policy is “guided by the science.” In practice they mean “our scientists,” and initial UK government policy was highly consistent with that advice. Ministers formed strong relationships with key scientific advisors, relied on evidence from their Scientific Advisory Group for Emergencies (SAGE), and ignored or excluded many other sources. I explore two types of lesson from this experience. First, UK studies of interest groups help explain the politics of expert advice. They show that the minister-adviser relationship is conditional on the ways in which the UK government assigns status to particular sources of science advice, and the willingness of those advisers to follow the “rules of the game,” within a wider political and policymaking context. Second, documentary analysis of SAGE minutes and meeting papers, and analysis of oral evidence to key House of Commons committees, shows high consistency between SAGE advice and UK government policy in the run up to lockdown. Ministers relied on their advisers to define the policy problem and identify feasible solutions throughout this period, while their advisors supported government policy and the right of ministers to make it. This new experience reflects and reinforces longstanding evidence from policy community studies: some experts remain core insiders if they advise on policies that they do not necessarily support, while outsiders have the freedom to criticize the policy they were unable to influence.